The moderating effect of social media usage on the relationship between personality trait and job performance in private sector in Jordan - Siam, Mohammed R A; Qaralleh, Samer Jibril (2017)
The prime objective of this study is to find the moderating role of social media usage on the relationship between personality traits and job performance.In addition to that we have also investigated the impact of personality traits on job performance.To meet the research objectives, we have used structural equation modeling technique on Smart PLS 2.0.The data was gathered from 391 employees of Al-MANSEER (Pvt) Ltd of Jordon. The findings of the study provide no evidence regarding the moderating effect of the social media usage.However, this study found a positive relation between five personality traits and job performance.This study will provide aid to human resource policy makers and trainers in assessing the impact of five personality traits on job performance and to access how social media usage moderate this relation.